Modeling the genetic complexity of Parkinson's disease by targeted genome edition in iPS cells. (October 2017) - Calatayud, Carles; Carola, Giulia; Consiglio, Antonella; Raya, Angel
Highlights: The genetic bases of Parkinson's disease (PD) are largely unknown. Recent studies have identified a large number of putative genetic risk factors for PD. Patient-specific iPSC models of familial and sporadic PD have been generated. CRISPR/Cas9-mediated gene modification has been used to edit risk variants in iPSC. The combination of iPSC and CRISPR/Cas9 technologies could be used to dissect the genetic complexity of PD. Abstract : Patient-specific iPSC are being intensively exploited as experimental disease models. Even for late-onset diseases of complex genetic influence, such as Parkinson's disease (PD), the use of iPSC-based models is beginning to provide important insights into the genetic bases of PD heritability. Here, we present an update on recently reported genetic risk factors associated with PD. We discuss how iPSC technology, combined with targeted edition of the coding or noncoding genome, can be used to address clinical observations such as incomplete penetrance, and variability in phenoconversion or age-at-onset in familial PD. Finally, we also discuss the relevance of advanced iPSC/CRISPR/Cas9 disease models to ascertain causality in genotype-to-phenotype correlation studies of sporadic PD.